The Current Trends of Optics and Photonics - Lee, Cheng-Chung.; Lee, Cheng-Chung. (Topics in Applied Physics,, 2015)
Optics and photonics offer new and vibrant approaches to meeting the challenges of the 21st century concerning energy conservation, education, agriculture, personal health and the environment. One of the most effective ways to address these global problems is to provide updated and reliable content on light-based technologies. Optical thin films and meta-materials, lasers, optical communications, light-emitting diodes, solar cells, liquid crystal technology, nanophotonics and biophotonics all play vital roles in enriching our lives. We hope to raise readers’ awareness of how optical technologies are now promoting sustainable development and providing reliable solutions to basic human needs. Furthermore, in order to broaden new research fields, we hope to inspire them to pursue further cutting-edge breakthroughs on the basis of the accomplishments that have already been made.